FERTILIZATION WITH BORON IN Corymbia citriodora SEEDLINGS - Pradela, V. A.; Lapaz, A. M.; Yoshida, C. H. P.; Nicolai, A. B.; Silva, K. A. M.; Tomaz, R. S. (Revista Brasileira de Engenharia de Biossistemas, 2018)
The formation of healthy and high-quality seedlings has fundamental importance for the cultivation of this species since it guarantees greater efficiency and resistance of the plant to edaphoclimatic conditions. Considering the importance of boron (B) for Corymbia citriodora in initial development and the absence of B in soils, the present work aimed to evaluate the benefits of B fertilization in Corymbia citriodora seedlings. The experimental design was completely randomized, comprising 5 treatments of B doses in the form of H3BO3 (0.0, 0.25, 0.50, 0.75 and 1.0 mg L-1). In a general way, under growing conditions, the dose 0.5 mg L-1 of B gave the most substantial increments for the parameters of the stem diameter; shoot and root length; and shoot and root dry mass. In the treatment without B (control), the smallest increments were detected for the evaluated parameters, showing that fertilizing with B is beneficial in these conditions of growth.